Corrective feedback in language teaching - Ellis, Rod; Sheen, Y. (Routledge, 2011)
Corrective feedback (CF) refers to the feedback that learners receive on the linguistic errors they make in their oral or written production in a second language (L2). Both oral and written CF have the attracted considerable attention in recent years because of their significance for the development of theories of L2 acquisition and because they have held an important place in L2 pedagogy. We begin with a brief description of what oral and written CF entail and then move on to consider a number of theories of L2 learning where CF holds a central place. We will then consider the key issues that surround the provision of CF language pedagogy. Finally, we review the empirical research that has investigated oral and written CF.